Pengembangan bahasa kemampuan berbicara anak usia dini melalui metode bercerita di kelompok bermain di Pati - Sri Wahyuningsih (STAI Syekh Jangkung, 2025)
Development of Early Childhood Language Speaking Skills Through the Storytelling Method in the Al – Mu'awanah Kayen Play Group Academic Year 2024 / 2025. Pati PG-PIAUD STAI Syekh Tall. 2024. This research is about Early Childhood Language Development through the media of a series of pictures with case studies of Al - Mu'awanah Kayen KB students in the 2004/2005 academic year. The researcher researched the development because there were problems in the speaking abilities of children in Al - Mu'awanah KB interesting to research or observe. This research aims to describe the speaking abilities of young children in the Al-Mu'awanah Kayen Pati Play Group. This research uses qualitative research methods with various techniques to collect data such as conducting interviews, observation and documentation. In the speech skills of early childhood at KB Al - Mu'awanah Kayen Pati there are 2 children who still need to pay attention, the first is that the child's speech development is still passive or when learning the child often plays alone, the second is the child whose speech development still lacks vocabulary. The child's daily speech often stutters but is not very fluent. In an effort to develop children's spoken language, namely expanding the storytelling method using storybooks and props. Not only telling the story in the story, but the storyteller or teacher expands the story with several other questions and provokes children's responses related to their hobbies, their interests. Aspects of language development using this series of image media include speaking, writing and telling stories. Keywords: Language Development, Early Childhood, Storytelling